A 1, 8-naphthalimide-based fluorescent sensor with high selectivity and sensitivity for Hg2+ in aqueous solution and living cells. Issue 25 (17th June 2019) - Liu, Daying; Zhu, Hualing; Shi, Jun; Deng, Xinxin; Zhang, Tingting; Zhao, Ye; Qi, Pengpeng; Yang, Guangming; He, Huarui
Abstract : A new 4-amino-1, 8-naphthalimide-based fluorescent sensor, with iminodiacetic acid and picolinic acid as receptors, was developed and applied successfully to detect Hg 2+ in aqueous solution and living cells. Abstract : A new 4-amino-1, 8-naphthalimide-based fluorescent sensor, with iminodiacetic acid and picolinic acid as receptors, was developed and applied successfully to detect Hg 2+ in aqueous solution and living cells. It demonstrates high selectivity and sensitivity for sensing Hg 2+ with about 25-fold enhancement with a characteristic emission band centered at 550 nm with a green color.